THEORETICAL AND METHODOLOGICAL PRINCIPLES OF USE OF HEALTH-CONSERVING INNOVATIVE TECHNOLOGIES IN THE EDUCATIONAL PROCESS OF MODERN EDUCATIONAL INSTITUTIONS - Жалій, Руслан (Modern engineering and innovative technologies, 2024)
The introduction of health-preserving technologies in the educational space of higher education is an urgent need and requirement of modern realities. The goal is to trace the features of the use of innovative health-preserving technologies in the process